Is caste destiny? Occupational diversification among dalits in rural India - Ira Gang; Kunal Sen; Myeong-Su Yun (Osteuropa-Institut Regensburg, 2011)
The caste system - a system of elaborately stratified social hierarchy - distinguishes India from most other societies. Among the most distinctive factors of the caste system is the close link between castes and occupations, especially in rural India, with Dalits or Scheduled Castes (SC) clustered in occupations that were the least well paid and most degrading in terms of manual labour. Along with the Scheduled Tribes (STs), the SCs have the highest incidence of poverty in India, with poverty rates that are much higher than the rest of the population. Since independence, the Indian government has enacted affirmative action policies in educational institutions and public sector employment for SCs and STs. In addition, in the more populous states of India, political parties have emerged that are strongly pro-SC in their orientation in the more populous states of India. We use five rounds of all-India employment data from the National Sample Survey quinquennial surveys from 1983 to 2004 to assess whether these political and social changes has led to a weakening of the relationship between low caste status and occupational segregation that has existed historically in India. We find evidence that the occupational structure of the SC households is converging to that of the non-scheduled households. However, we do not find evidence of a similar occupational convergence for ST households.
Keywords: 330; caste; occupational diversification; poverty; India; Soziale Schicht; Berufsstruktur; Arbeitsmarktdiskriminierung; Armutspolitik; Wirkungsanalyse; Indien